The effect of insurance status on treatment modality in advanced oral cavity cancer - Shanmugappiriya Sivarajah; Daniel Ghods-Esfahani; Alexandra Quimby; Fawaz Makki; Giacomo Montagna; Hadi Seikaly (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Insurance status has been shown to impact survival outcomes. We sought to determine whether insurance affects the choice of treatment modality among patients with advanced (T4) oral cavity squamous cell carcinoma. Methods This is a retrospective, population-based cohort study using the Survival, Epidemiology, and End Results Program database. The population included all adult (age ≥ 18) patients with advanced (T4a or T4b) oral cavity squamous cell carcinoma diagnosed from 2007 to 2016. The main outcome was the odds of receiving definitive treatment, defined as primary surgical resection. Insurance status was categorized into uninsured, any Medicaid, and insured groups. Univariable, multivariable, and subgroup analyses were performed. Results The study population consisted of 2628 patients, of whom 1915 (72.9%) were insured, 561 (21.3%) had Medicaid, and 152 (5.8%) were uninsured. The multivariable model showed that patients who were 80 years or older, unmarried, received treatment in the pre-Affordable Care Act (ACA) period, and who were on Medicaid or uninsured were significantly less likely to receive definitive treatment. Insured patients were significantly more likely to receive definitive treatment compared to those on Medicaid or uninsured (OR = 0.59, 95% CI 0.46–0.77, p < 0.0001 [Medicaid vs. Insured]; and OR = 0.48, 95% CI 0.31–0.73 p = 0.001 [Uninsured vs. Insured]), however these differences did not persist when considering only those patients treated following the 2014 expansion of the ACA. Conclusions Insurance status is significantly associated with treatment modality among adults with advanced stage (T4a) oral cavity squamous cell carcinoma. These findings support the premise of expanding insurance coverage in the US. Graphical Abstract